Pengembangan Masyarakat Islam dalam Sistem Dakwah Islamiyah - Mukhlis Aliyudin (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2009)
For moslem community, da’wah hold essential role with the importance for with development, and even that da’wah the reality is development. Amends and don't it a community (ummat) really hinges on intensity and da’wah quality that did by moslems. With da’wah moslems can get role in engineers the moslem community social living well in social, economy, culture, politics, even it’s no impossible will make them as “ trend setted “ and main factor and actor in changed social development. Da’wah constitutes aware job in order to uphold justice, increasing welfare, enriching equation, and reaches happiness.